Ancient goldworking technology in Butuan, Northeastern Mindanao, Philippines. - Estrella, Victor P. (July 2017)
This master's thesis examines the worked gold items, as well as, the associated non-gold items recovered in sites in Butuan, Northeastern Mindanao, Philippines. These archaeological materials are part of a sub-assemblage deemed to belong to goldworking activities operating from the 10th to the 15th century CE. This research porject employed material analysis and technical study on the observable morphology of the artefacts, particularly of the gold items, in order to identify goldworking techniques involved both in their production. This study argues that goldworking in Butuan involved both physical and cognitive activies, and that the goldworks are therefore products of both the manufacturing techniques and the gold standards and conventions observed in the Southeast Asian region during this time. The examination of the sequence of gold objects'physical production can reveal the technology and the society in which the artisan is at the centre. In putting together the archaeological data and the historical and ethnographic records, this study tries to present the social dimension of this technology.
Thesis (M.A. Archaeology) -- University of the Philippines, Diliman